1967
DOI: 10.1507/endocrj1954.14.308
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Gonadotropin Inhibiting Substance on Super-Ovulation Induced by Pregnant Mare Serum Gonadotropin and Human Chorionic Gonadotropin

Abstract: The effect of a gonadotropin (luteinizing hormone) inhibiting substance on the ovarian histology and the super-ovulation induced by the injections of PMSG and HCG with an interval of 45 hours was studied in immature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1969
1969
1979
1979

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It was previously shown that Samples NA and PPT obtained from urine specimens of the same subjects collected at different periods showed the inhibitory effect on the ovulation induced by PMS and HCG (Ota et al, 1967b(Ota et al, , 1968c. Samples NA and PPT contained higher amounts of sialic acid and this was only the difference in the amounts of these substances found between Sample SA and Sample NA or PPT.…”
Section: Resultsmentioning
confidence: 85%
“…It was previously shown that Samples NA and PPT obtained from urine specimens of the same subjects collected at different periods showed the inhibitory effect on the ovulation induced by PMS and HCG (Ota et al, 1967b(Ota et al, , 1968c. Samples NA and PPT contained higher amounts of sialic acid and this was only the difference in the amounts of these substances found between Sample SA and Sample NA or PPT.…”
Section: Resultsmentioning
confidence: 85%
“…That GIM has specific LH-inhibiting properties has been reported by a number of investigators (3,8,14). This may be effected if GIM binds itself to the LH/hCG molecule, thus making the hormone unavailable to the target cell receptors as the new molecule would not be recognized by the LH receptors.…”
Section: Discussionmentioning
confidence: 97%
“…However, serious limitations for quantitative estimations are encountered due to the unsuitability of the bioassay procedures employed. Percentage reduction of mouse uterine weight (Landau et al, 1960;Futterweit et al, 1963;Mahajan and Shah, 1966;Sairam et al, 1966;Hipkin, 1967), inhibition of PMS induced ovulation in rats (Lastra and Arrau, 1967) and mice (Ota et al, 1967) and the inhibition of compensatory ovarian hypertrophy in mice (Benson et al, 1972) are some of the bioassay end points. The methods thus detect only the presence of anti-gonadotropin activity in a given aliquot but cannot give a precise quantitation of this material per 24 hrs.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence available at present is insufthough both the hypothalamus (Lastra and Arrau, 1967;Mahajan and Shah, 1970;Shah and Kothari, 1970) and the pineal (Soffer et al, 1965;Hipkin, 1970;Benson et al, 1972) have been suggested. Inspite of a number of reports on this subject the available assay systems (Landau et al, 1960;Futterweit et al, 1963;Mahajan and Shah 1966;Sairam et al, 1966;Hipkin 1967;Lastra and Arrau 1967;Ota et al, 1967;Benson et al, 1972) can only indicate whether the inhibitor is present or not and are ineffective as far as precise quantitation is concerned. Since this substance present in urine of man has been shown to be specifically anti-LH (Soffer and Fogel 1963), we attempted to take advantage of this property to assay it in terms of anti-HCG units.…”
mentioning
confidence: 99%